2009
DOI: 10.4049/jimmunol.0901390
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Borrelia burgdorferi, the Lyme Disease Spirochete, by TLR7 and TLR9 Induces a Type I IFN Response by Human Immune Cells

Abstract: Borrelia burgdorferi is the spirochetal agent of Lyme disease, a multisystemic disorder characterized by inflammation. Using global transcriptional profiling, we characterized the response of human PBMCs exposed to B. burgdorferi in an ex vivo coculture system. The expression profiles induced by B. burgdorferi were marked by the intense up-regulation of IFN-responsive transcripts and transcripts involved in the JAK/STAT signaling pathway. Transcript levels of IFN-α, IFN-β, and IRF7, and protein concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
136
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(150 citation statements)
references
References 121 publications
(105 reference statements)
10
136
2
2
Order By: Relevance
“…Specific immunoregulatory DNA sequences (IRSs; Integrated DNA Technologies) (31) were used to block TLR7 signaling (IRS661: 5′-TGCTTGCAAGCTTGCAAGCA-3′), TLR7 and TLR8 (IRS957: 5′-TGCTTG-AC-ATCCTGGAGGGGTTGT-3′), and TLR9 (IRS869: 5′-TCCTGGAGGGGTTGT-3′) as described by Petzke et al (22). A non-TLR-specific oligodeoxyribonucleotide sequence was used as a control, in the same concentration as the TLR inhibitor.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Specific immunoregulatory DNA sequences (IRSs; Integrated DNA Technologies) (31) were used to block TLR7 signaling (IRS661: 5′-TGCTTGCAAGCTTGCAAGCA-3′), TLR7 and TLR8 (IRS957: 5′-TGCTTG-AC-ATCCTGGAGGGGTTGT-3′), and TLR9 (IRS869: 5′-TCCTGGAGGGGTTGT-3′) as described by Petzke et al (22). A non-TLR-specific oligodeoxyribonucleotide sequence was used as a control, in the same concentration as the TLR inhibitor.…”
Section: Methodsmentioning
confidence: 99%
“…Bacteria can elicit type I IFNs either by activating TLRs (11,12) or through TLR-independent recognition of bacterial pathogenassociated molecular patterns (PAMPs) within the host cell cytosol (11,18). We and others have begun to demarcate the pathways by which live Bb induces type I IFNs in both mouse and human cells (7,(19)(20)(21)(22). Miller et al (20) demonstrated that live Bb induces transcription of several ISGs in bone marrow-derived murine macrophages (BMDMs) independent of both MyD88 (20) and TRIF (21) yet requiring the transcription factor IFN regulatory factor (IRF) 3.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Niedobór TRIF nie wpływa jednak, w przeciwieństwie do niedoboru MyD88, na osłabienie odpowiedzi na infekcję krętkami u myszy [36]. W rozpoznaniu Borrelia burgdorferi biorą udział również receptory TLR7 i TLR9, indukując wydzielanie interferonu przez komórki immunologiczne [37].…”
Section: Choroby Infekcyjne Skóryunclassified